2019
DOI: 10.1080/09638288.2019.1577504
|View full text |Cite
|
Sign up to set email alerts
|

Views of children with cerebral palsy and their parents on the effectiveness and acceptability of intensive speech therapy

Abstract: Purpose: To understand children and parents' views of the effectiveness and acceptability of intensive dysarthria therapy. Materials and Methods: Twenty-two children with cerebral palsy and dysarthria joined a pilot RCT comparing intensive therapy and usual care. Children (n ¼ 11) allocated to dysarthria therapy comprising three 40-minute sessions per week for six weeks and their parents (n ¼ 11) were interviewed two weeks before and six weeks after therapy. Interviews were transcribed verbatim and analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The general responses showed that treatment intensity was well tolerated, although parents were concerned about maintaining practice time needed to maintain healthy voice quality and generalization of skills to everyday communication. The qualitative analyses of POST interviews and treatment ratings show some initial evidence of intensive treatment effectiveness and parents' desire and willingness to commit and participate in the structured LSVT LOUD protocol similar to other groups of parents who participated in LSVT LOUD or an intensive Speech Systems Approach with children who have CP Fox & Boliek, 2012Pennington et al, 2019.…”
Section: Parent Ratings Of Treatment and Post-treatment Interviewsmentioning
confidence: 78%
See 1 more Smart Citation
“…The general responses showed that treatment intensity was well tolerated, although parents were concerned about maintaining practice time needed to maintain healthy voice quality and generalization of skills to everyday communication. The qualitative analyses of POST interviews and treatment ratings show some initial evidence of intensive treatment effectiveness and parents' desire and willingness to commit and participate in the structured LSVT LOUD protocol similar to other groups of parents who participated in LSVT LOUD or an intensive Speech Systems Approach with children who have CP Fox & Boliek, 2012Pennington et al, 2019.…”
Section: Parent Ratings Of Treatment and Post-treatment Interviewsmentioning
confidence: 78%
“…The need to assess parent perceptions of treatment and treatment results is in line with the need to describe patient-reported outcomes in the more general context of today's health care models (de Riesthal & Ross, 2015). Moreover, as Pennington et al point out (Pennington et al, 2019), qualifying child and parent views on treatment and perceived outcomes is an important component toward establishing treatment effectiveness in later stages of evidence (Robey, 2004).…”
Section: Parent Ratings Of Treatment and Post-treatment Interviewsmentioning
confidence: 99%
“…Each focus group will include up to 10 participants. Responses to the focus groups will be analyzed by an RA using thematic analysis, following the same methods employed in a similar study with children with cerebral palsy [ 31 ], that is, inductive thematic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In this treatment, participants focused on the stabilization of respiration, phonation and speech rate at various linguistic levels. Positive gains in speech intelligibility have been reported following treatment in both younger children (Pennington et al., 2013) and older children (Pennington et al., 2010a) with CP. However, a possible limitation of this treatment approach is its use of multiple instructions, a potential confounding factor in light of the comorbid language‐learning deficits commonly noted in individuals with CP (Beckung & Hagberg, 2002).…”
Section: Speech Treatments For Developmental Dysarthriamentioning
confidence: 99%
“…This approach targets improved functioning of several speech subsystems (e.g., phonation, respiration, prosody), without directly targeting articulatory skills. It is based on the notion that speech sound production and overall intelligibility are impacted by impaired functioning at the levels of the respiration, phonation and prosody (Pennington et al., 2010a). In this treatment, participants focused on the stabilization of respiration, phonation and speech rate at various linguistic levels.…”
Section: Speech Treatments For Developmental Dysarthriamentioning
confidence: 99%